Elección coherente de los formatos de digitalización de la documentación del paciente - RAMOS-LÓPEZ, Juan Manuel; CUCHÍ ALFARO, Miguel; SÁNCHEZ RUIZ, Domingo (Revista General de Información y Documentación, 2010)
Document scanning is being implemented currently in the management of patients in the hospital environment to translate the document with signatures, handwritten notes, etc. We must have computer knowledge in terms like pixels, resolutions, compression, etc, to choose correctly the storage images. The applicative Web technology is developed showing the images embedded in the same window. The scanners used for digitizing documents can set software profiles with the storage features of TIFF files. Format errors in resulting files were analyzed using free software utilities for processing Tiffs.127,461 documents were checked with an average of 2 pages (standard deviation 2) and with an error rate in compression or resolution of 1.9%. The types of errors was related to the document type and complexity (chi-square p
Keywords: Technology and Innovation Management; Automatic Data Processing; Digital Libraries; Hospital Information Systems